Exploring e-governance service delivery dimensions: a study of Registrar of companies - Kaur, Amandeep; Kaur, Harpreet (2017)
E-governance is becoming a phenomenon that is catching the attention of government as well as the citizens across the world. Lately, the governments of almost all the countries of the world made huge investments in implementation of e-government projects including India. There have been a number of centre- and state-level projects launched in the recent years. Hence, it becomes all the more important to assess the impact and viability of such projects. A number of studies have been undertaken in this area. It is observed that most of the studies in this field have focused on exploring e-governance service delivery dimensions in government-to-citizen (G2C) context; however, a few studies are carried out in government-to-business (G2B) context. Hence, the present study is an attempt to bridge this gap. The study aims to explore e-governance service delivery dimensions as perceived by the employees of Registrar of Companies (ROC), North Region. Ninety employees of ROCs were surveyed to know about their perception about the pioneer e-government project named Ministry of Corporate Affairs of 21st Century (MCA21) launched in 2006. Results of the study identified four dimensions as perceived important by the employees. To improve the services provided by the employees to the users, it would be useful to be aware of these dimensions in the future. - Reproduced.
Keywords: Case study - Office of registrar of companies; Service delivery; Information and communication technology; Government to business (G2B); Government and Business; E-governance